Entrepreneurship Education and Student Intention to Launch a Business: Does Entrepreneurial Knowledge and Skills Acquisition Act as a Mediator? - Edokpolor, James Edomwonyi; Osebhakhome Imeokparia, Patience; Osifo, Kessington (Journal of Technology Management and Business, 2023)
This paper examined the mediating role of entrepreneurship knowledge and skill acquisition (EKSA) in the interaction between entrepreneurship education (EE) and students' intention to launch a business (SILB), in the case of Nigeria. A quantitative correlational design was adopted for the study. A structured questionnaire was used for data collection. The questionnaire for data collection was validated once by three experts, two from the field of business education and one from the field of measurement and assessment. Pearson's correlation statistic, linear regression statistic and bias-corrected bootstrapping technique were performed to analyse the data collected from a randomly selected sample of 412 university students. The results of the Pearson’s correlation analysis showed a significant correlation among EE, EKSA and SILB. The results of the linear regression analysis also indicated a significant association among EE, EKSA and SILB. The results of the bias corrected bootstrapping technique also showed that EKSA mediates the association between EE and SILB. The results showed the extent of association between EE and SILB and offer some logical implications for curriculum designers, university students and university administrators. This study contributed significantly to EE, EKSA and SILB literature.